Pengaruh Persepsi Kemudahan Dan Persepsi Kegunaan Pada Platform Investasi Digital Terhadap Sikap Dan Minat Investasi Generasi Milenial Di Kota Malang - Antin Rakhmawati; Nurma Leny Yanatul Hikmah; Abdul Aziz Fuadi (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
The current millennial generation also utilizes digital technology to make investments, such as transacting through digital investment platforms. However, it still depends on the perception of convenience and usefulness. This phenomenon creates a potential market for digital investment platforms, but it also raises questions about how literate millennials are about financial information and how their perception of the platform influences their investment decisions. This research was conducted with the aim of determining the Influence of Perception of Convenience and Perception of Usability on Digital Investment Platforms on the Attitude and Investment Interest of the Millennial Generation in Malang City. The sample used in this study is the millennial generation who are using one of the Digital Investment Platforms with a total of 106 respondents.  The research method in this study is the Quantitative Method and data are obtained from the distribution of Questionnaires offline and online. This study uses the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) models. Data processing is carried out using the SPSS version 25 application. The results obtained in this study are that the variables of perception of convenience and perception of usability have a significant positive effect on the variables of the attitude of users of the Digital Investment platform. In addition, the variable of perception of convenience has a significant positive effect on the interest of investment users.  Then, in the variable of perception of usability to the variable of user interest of digital investment platforms, it is significant but not statistically fulfilled. Meanwhile, the attitude variable has a significant positive effect on the variable of interest of investment platform users.